Higher Order Thinking Skills (Hots) In The Discovery Learning - Fitria, Wilma; Putra, Kasman Edi; Hidayat, Adityawarman (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
This research was motivated by the lack higher order thinking skill (HOTS) of class VIII students of SMP Negeri 2 Rumbio Jaya. One of the solution to overcome this problem is to use an discovery learning model. The purpose of this study was to determine differences in the higher order thinking skill (HOTS) of students who applied the discovery learning model to students who applied conventional learning. This research is a quasi-experimental using  non-equivalent control group design. The research subjects consisted of class VIIIA totaling 24 students and VIII B totaling 24 students. The sample technique used was purposive sampling. Data collection techniques used ware observation sheets and higher order thinking skill (HOTS) test questions. The results shows that there is a difference in the average test results of students' higher order thinking skill (HOTS) in the experimental class using the discovery learning model with the control class applying conventional learning to class VIII students of SMP Negeri 2 Rumbio Jaya. This can be proven through the Independent Sample T-Test obtaining a sig(2-tailed) value of 0.000<0.05, then H0 is rejected and H1 is accepted. Testing the post-test hypothesis with the Independent Sample T-Test above shows that the Levene’s test results are homogeneous for both data variances, so the calculated t value that can be used is  3.949 with sig(2-tailed) 0.000 < 0.05, so H0 is rejected and H1 is accepted . So it can be concluded that there is an influence of the Discovery Learning model on increasing Higher Order Thinking Skill in Class VIII SMPN 2 Rumbio Jaya.